Germinação e crescimento inicial de milho sob aplicação de biofertilizantes inoculados com Azospirillum brasilense - Castro, Rones dos Santos (2017)
Fish waste is often deposited indiscriminately in the environment. These wastes can be used in the production of biofertilizers, easily produced by the farmer. In addition to providing nutrients, biofertilizers can provide microorganisms. Azospirillum brasilense is a diazotrophic bacteria capable of saving nitrogenous fertilizers and improving the growth and development of maize plants (Zea mays L). The aim of this work was to evaluate the use of biofertilizers produced with fish waste inoculated with A. brasilense on the initial growth of maize plants. The experimental design was completely randomized according to the factorial arrangement 2 x 5 + 1, with four replications. The treatments consisted of the combination of the absence or presence of A. brasilense in biofertilizers produced with five substitutions of the bovine manure component for fish waste: BIO 100EB:0RP; BIO 75EB:25RP; BIO 50EB:50RP; BIO 25EB:75RP; and BIO 0EB:100RP. Biofertilizers based exclusively on fish waste or those in association with bovine manure had a negative influence on the prevalence of the A. brasilense bacteria and on the contrary for the biofertilizers produced exclusively with bovine manure. The germination of AG 1051 maize hybrid seeds was not affected by 10% solution of biofertilizers, inoculated or not with A. brazilense bacteria. The growth of AG 1051 maize hybrid, evaluated at 45 days after sowing in the conditions of the present study, was, in general, positively influenced by the application of a 20% solution of biofertilizers based exclusively on fish waste and inoculation of A. brasilense bacteria.